A highly efficient quantum dot light emitting diode via improving the carrier balance by modulating the hole transport. Issue 69 (7th September 2017) - Pan, Jiangyong; Chen, Jing; Huang, Qianqian; Wang, Lixi; Lei, Wei
Abstract : A highly efficient solution-processed QLED device with a doped HTL has been demonstrated by the modulation of hole transport. Abstract : A high-performance solution processed quantum dot light emitting diode (QLED) has been fabricated via modulating the hole transport by doping 1-bis[4-[ N, N -di(4-tolyl)amino]phenyl]-cyclohexane (TAPC) into poly- N -vinylcarbazole (PVK) as the hole transport layer (HTL). With a low doping content, the hole transport ability of the HTL can be enhanced due to the extremely high hole mobility of TAPC. However, increasing the doping ratio of TAPC excessively results in degraded performance of the QLED due to the deteriorated film quality and increased energy barrier from the HTL to the quantum dots (QDs), which is attributed to the relatively shallow position of the HOMO level for TAPC. Using the optimized composition ratio of the doped HTL (3 : 1 vol% of PVK : TAPC), the best QLED performance was achieved with a low turn-on voltage of 3.3 V due to the charge balance, which facilitates exciton recombination in the emissive layer (EML). In addition, the highest current efficiency (26.2 cd A −1 ), power efficiency (19.2 lm W −1 ), external quantum efficiency (6.2%) and 60% enhancement in the stability of the device were achieved. The improvement in the device performance can be attributed to the suppression of Auger recombination due to the balance of carrier injection into the emissive layer composed of QDs and the separation of the carrier accumulation zone from the exciton formation interface by the modulation of hole transport. The lowered turn-on voltage and improved efficiency presented here offer potential for high throughput and practical use for commercialized QLED displays.